K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: \(\Leftrightarrow5x\left(x^2-6x+9\right)-5\left(x^3-3x^2+3x-1\right)+15\left(x^2-4\right)=5\)

\(\Leftrightarrow5x^3-30x^2+45x-5x^3+15x^2-15x+5+15x^2-20=5\)

\(\Leftrightarrow30x-15=5\)

hay x=2/3

b: \(\Leftrightarrow x^3+9x^2+27x+27-9x^3-6x^2-x+8x^3+1-3x^2=42\)

\(\Leftrightarrow26x+28=42\)

=>26x=14

hay x=7/13

a: \(\Leftrightarrow5x\left(x^2-6x+9\right)-5\left(x^3-3x^2+3x-1\right)+15x^2-60-5=0\)

\(\Leftrightarrow5x^3-30x^2+45x-5x^3+15x^2-15x+5+15x^2-65=0\)

\(\Leftrightarrow30x-60=0\)

hay x=2

b: \(\Leftrightarrow x^3+9x^2+27x+27-x\left(9x^2+6x+1\right)+8x^3+1-3x^2=42\)

\(\Leftrightarrow9x^3+6x^2+27x+28-9x^3-6x^2-x=42\)

=>26x=14

hay x=7/13

24 tháng 7 2017

\(a,5x\left(x-3\right)^2-5\left(x-1\right)^3+15\left(x+2\right)\left(x-2\right)=5\)\(\Leftrightarrow5x\left(x^2-6x+9\right)-5\left(x^3-3x^2+3x-1\right)+15\left(x^2-4\right)-5=0\)\(\Leftrightarrow5x^3-30x^2+45x-5x^3+15x^2-15x+5+15x^2-60-5=0\)\(\Leftrightarrow30x=60\Leftrightarrow x=2\)

\(b,\left(x+3\right)^3-x\left(3x+1\right)^2+\left(2x+1\right)\left(4x^2-2x+1\right)-3x^2=42\)\(\Leftrightarrow x^3+9x^2+27x+27-x\left(9x^2+6x+1\right)+8x^3+1-3x^2-42=0\)\(\Leftrightarrow x^3-9x^2+27x+27-9x^3-6x^2-x+8x^3+1-3x^2-42=0\)\(\Leftrightarrow26x=14\Rightarrow x=\dfrac{7}{13}\)

Học tốt nha<3

a: \(\Leftrightarrow5x\left(x^2-6x+9\right)-5\left(x^3-3x^2+3x-1\right)+15x^2-60-5=0\)

\(\Leftrightarrow5x^3-30x^2+45x-5x^3+15x^2-15x+5+15x^2-65=0\)

\(\Leftrightarrow30x-60=0\)

hay x=2

b: \(\Leftrightarrow x^3+9x^2+27x+27-x\left(9x^2+6x+1\right)+8x^3+1-3x^2=42\)

\(\Leftrightarrow9x^3+6x^2+27x+28-9x^3-6x^2-x=42\)

=>26x=14

hay x=7/13